REALITIES AND PROSPECTS OF SOCIAL REHABILITATION OF THE FAMILIES OF MILITARY PERSONNEL IN THE CONDITIONS OF WAR - Аксьонова, Катерина (Київський національний університет імені Тараса Шевченка, 2024)
B a c k g r o u n d . In today's conditions, professional assistance aimed at restoring the mental, social well-being and economic stability of the citizens of Ukraine is of great importance. Among a number of social practices that are in demand and actualized in the conditions of modern challenges, the leading place belongs to social rehabilitation work. The realities and prospects of social rehabilitation in modern Ukrainian society are considered. The importance of social rehabilitation as a means of solving the needs of military personnel's families and alleviating the difficulties they face at many levels is explored. M e t h o d s . In the research process, methods of theoretical analysis of scientific publications, comparative analysis of regulatory documents, methods of cognitive-behavioral therapy, relaxation training and stress management were applied. Social transformations, the impact of changes and upheavals in wartime conditions are analyzed. Challenges to Ukrainian society caused by Russia's military aggression against Ukraine are singled out, including financial instability, emotional trauma, social isolation and tension in family relationships. The role of social rehabilitation in providing a comprehensive approach to support of military personnel's families, taking into account their physical, psychological and social well-being, is indicated. R e s u l t s . The structural components of social rehabilitation of military personnel's families were determined, the approaches of foreign and Ukrainian researchers and practitioners to the disclosure of this problem were analyzed. Modern social rehabilitation initiatives implemented by state institutions, nonprofit and charitable organizations are highlighted. C o n c l u s i o n s . Prospects for improving social rehabilitation programs, which advocate expanding access to mental health services, improving financial support systems, expanding educational opportunities for children, and improving employment assistance for spouses, are considered. The problems of social rehabilitation of military personnel's families, which in the conditions of the full-scale invasion of Russia into Ukraine are separated into the theory and practice of social rehabilitation, are updated. Ways of providing the necessary support to the families of the military personnel, which will allow them to overcome the difficulties of the war and rebuild their lives, are proposed.

В с т у п . В умовах сьогодення великого значення набуває фахова допомога, спрямована на відновлення психічного та соціального добробуту, економічної стабільності громадян України. Серед ряду соціальних практик, затребуваних і актуалізованих в умовах сучасних викликів, провідне місце належить соціально-реабілітаційній роботі. Розглянуто реалії та перспективи соціальної реабілітації у сучасному українському соціумі. Досліджено важливість соціальної реабілітації як засобу вирішення потреб сімей військовослужбовців і полегшення труднощів, з якими вони стикаються на багатьох рівнях. М е т о д и . У процесі дослідження застосовано методи теоретичного аналізу наукових публікацій, порівняльного аналізу нормативно-правових документів, методи когнітивно-поведінкової терапії, навчання релаксації та управління стресом. Проаналізовано соціальні трансформації, вплив змін і потрясінь в умовах воєнного часу. Виокремлено виклики українському суспільству, спричинені військовою агресією росії проти України, зокрема фінансова нестабільність, психічні травми, соціальна ізоляція та напруженість у сімейних стосунках. Вказано на роль соціальної реабілітації у забезпеченні комплексного підходу до підтримки сімей військовослужбовців з урахуванням їхнього фізичного, психологічного та соціального добробуту. Р е з у л ь т а т и . Визначено структурні компоненти соціальної реабілітації сімей військовослужбовців, проаналізовано підходи зарубіжних та українських дослідників, практиків щодо розкриття цієї проблематики. Висвітлено сучасні соціально-реабілітаційні ініціативи, які реалізують державні установи, неприбуткові та благодійні організації. В и с н о в к и . Розглянуто перспективи вдосконалення програм соціальної реабілітації, які виступають за розширення доступу до послуг у сфері забезпечення психічного здоров'я, покращення систем фінансової підтримки, розширення можливостей освіти для дітей та покращення допомоги у працевлаштуванні для подружжя. Актуалізовано проблеми соціальної реабілітації сімей військовослужбовців, які в умовах повномасштабного вторгнення росії в Україну виокремлюються в теорію і практику соціальної реабілітації. Запропоновано шляхи надання необхідної підтримки сім'ям військовослужбовців, які дозволять їм подолати труднощі війни та налагодити своє життя заново.
РЕАЛІЇ ТА ПЕРСПЕКТИВИ СОЦІАЛЬНОЇ РЕАБІЛІТАЦІЇ СІМЕЙ ВІЙСЬКОВОСЛУЖБОВЦІВ В УМОВАХ ВІЙНИ
Keywords: distress; psychological trauma; readaptation; resocialization; social rehabilitation; social work; відновлення; дистрес; психологічна травма; реадаптація; ресоціалізація; соціальна реабілітація; соціальна робота